Virtual screening of ultra-large chemical libraries identifies cell-permeable small-molecule inhibitors of a “non-druggable” target, STAT3 N-terminal domain - Bonilla, Pedro Andrade; Hoop, Cody L.; Stefanisko, Karen; Tarasov, Sergey G.; Sinha, Sourav; Nicklaus, Marc C.; Tarasova, Nadya I. (Frontiers in Oncology, 2023)
STAT3 N-terminal domain is a promising molecular target for cancer treatment and modulation of immune responses. However, STAT3 is localized in the cytoplasm, mitochondria, and nuclei, and thus, is inaccessible to therapeutic antibodies. Its N-terminal domain lacks deep pockets on the surface and represents a typical "non-druggable" protein. In order to successfully identify potent and selective inhibitors of the domain, we have used virtual screening of billion structure-sized virtual libraries of make-on-demand screening samples. The results suggest that the expansion of accessible chemical space by cutting-edge ultra-large virtual compound databases can lead to successful development of small molecule drugs for hard-to-target intracellular proteins